PENGARUH KUALITAS PELAYANAN DAN POSITIONING TERHADAP KEPUTUSAN MENGINAP DI HOTEL SEVEN DREAM SYARIAH - Muhyiddin, Ahmad; Yuliandari, Ni Kadek (ESA : JURNAL KAJIAN EKONOMI SYARIAH, 2023)
This study aims to test and analyze the effect of service quality and positioning on overnight stay decisions at the Seven Dream Syariah Jember hotel. This study uses independent variables, namely service quality and positioning and the dependent variable is the decision to stay overnight. This research design is included in confirmatory research and explanatory research. Data were obtained through the distribution and collection of questionnaires and then analyzed using Multiple Linear Regression analysis. From the discussion and testing of the effect of service quality and positioning on the decision to stay at the Seven Dream Syariah Jember hotel, it turns out that service quality affects the decision to stay at the Seven Dream Syariah Jember hotel. Positioning affects the decision to stay at the Seven Dream Syariah Jember hotel.